TUM4Health, a holistic student health promotion program. Screening of cardiovascular risk factors in university students - Klaus Christian Haggenmüller; Barbara Reiner; Renate Maria Oberhoffer; Nils Olson; Jochen Weil; Thorsten Schulz (Frontiers in Cardiovascular Medicine)
Cardio Vascular risk prevention in Germany has a gap between the ages of 20 and 30 years. We established a program for risk group identification in students and analyzed the screenings according to the ACCF/AHA Stages and NYHA functional classification. In a cross-sectional design, 596 participants completed a sports medical and motor performance check-up. We found 6% of the female subgroup in an underweight status. Low blood pressure in 5% of the male and 10% of the female group. Elevated blood pressure in 27% of the male and 12% of the female subgroup. According to ACCF/AHA classification, a percentage of 25.7% were clustered in Stage A, defined as having a high risk for heart failure (HF). Stage B consisted of participants with structural heart disease but without symptoms of HF, the prevalence of this group was 3.2%. In Stage C we assigned 0.7%, respectively four participants, with structural heart disease and prior symptoms (NYHA Stage C1 and C2). Screenings sensitize CV risk factors and detect HF risks at an early age; for freshmen at universities it seems to be the perfect time and place for secondary prevention. The gap in risk prevention can be closed, at least for students, who are an economically important target group. Moreover, we found a higher prevalence of Stage C in the sports-related study population compared to other studies. The risk for HF could be elevated in sports-related faculties. The high prevalence of underweight participants, especially in the female subgroup could also be a specific problem in sports-related groups. Even if not related to CV risks, the awareness of being underweight in combination with offers for a lifestyle change can prevent risks in the future. The same applies to low blood pressure in the female subgroup.